An environmental and historical reading of Kant's "Critique of Teleological Judgement". - Bussmann, Michael. (University of Ottawa (Canada), 1995)
In this thesis I have presented the central passages of the 'Critique of Teleological Judgement' which outline Kant's view of final ends. In Chapter 1, I considered physical ends which Kant equates with organisms. I outlined his distinction between such ends and machines, namely the sense in which the parts of an organism are reproductive of the other parts, while in a machine they are not. In the second chapter, I went on to consider Kant's rejection of dogmatic teleology by way of his many examples. Following this, I explained Kant's understanding of extrinsic finality as a relationship of proximate use. In Chapter 3, I described Kant's argument against any organism, understood as a physical being, acting as the ultimate end of nature. And finally, in the fourth and final chapter of exegesis, I outlined Kant's assertion that the final end of creation is the group of individual moral rational beings. In the fifth chapter, I sought to offer an environmental assessment of Kant's views as representative of the humanist tradition. (Abstract shortened by UMI.)
Keywords: Philosophy.